The Importance of Recognizing Wandering Spleen as a Cause of Recurrent Acute Pancreatitis. (21st June 2018) - Lourdusamy, Vennis; Patel, Dhrumil; Docobo, Ramon; Tantry, Shyamanand; Lourdusamy, Dennis; Farukh, Saeed
Abstract : Wandering spleen, as its name suggests, is a rare condition where the spleen wanders in the abdomen and is most commonly found in the inferior quadrant as a palpable mass. It can have varying presentations and commonly presents as splenic torsion and very rarely as acute pancreatitis. It is imperative not to miss this diagnosis as it can lead to life-threatening complications in the form of splenic torsion/infarction. Here we describe a rare manifestation of wandering spleen where a young female presented with recurrent episodes of acute pancreatitis.